Assessment of ischemic penumbra in human hyperacute stroke patients using amide proton transfer (APT) Chemical Exchange Saturation Transfer (CEST) MRI - Tietze, Anna (2013)
Chemical exchange saturation transfer (CEST)-derived pH-weighted Amide Proton Transfer (APT) MRI has shown promise in animal studies for predicting infarction risk in ischemic tissue. Here, APT MRI was translated to acute human stroke patients (1–24 hrs post-symptom-onset) and assessments between APT contrast, perfusion, diffusion, disability, and final infarct volume (23–92 days post-stroke) are reported. Healthy volunteers (n=5) and patients (n=10) with acute onset of symptoms (0–4h: n=7; uncertain onset <24h: n=3) were scanned with diffusion- and perfusion-weighted MRI, FLuid Attenuated Inversion Recovery (FLAIR) and CEST. Traditional asymmetry as well as a Lorentzian-based APT index were calculated in the infarct core, at-risk tissue (time-to-peak, TTP, lengthening), and the final infarct volume. On average (mean±s.d.), control white matter APT values (asymmetry: 0.019±0.005; Lorentzian: 0.045±0.006) were not significantly different (P>0.05) than APT values in normal-appearing-white-matter (NAWM) of patients (asymmetry: 0.022±0.003; Lorentzian: 0.048±0.003), however ischemic regions in patients had reduced (P=0.03) APT effects compared to NAWM. Representative cases are presented whereby the APT contrast is compared quantitatively to contrast from other imaging modalities. Findings vary between patients; in some patients a trend for a reduction of the APT signal in the final infarct region compared to at-risk tissue was observed, consistent with tissue acidosis. However, in other patients no relationship was observed in the infarct core and final infarct volume. Larger clinical studies in combination with focused efforts on sequence development at clinically available field strengths (e.g., 3.0T) are necessary to fully understand the potential of APT imaging for guiding hyperacute management of patients.